Extracellular matrix proteins in hypoxia, 3D cancer spheroids as a model - Tamanna, Ifrat (My University, 2022)
The extracellular matrix (ECM) is a non-cellular network of cross-linked macromolecules, such as collagens, glycoproteins (fibronectin and laminins), and proteoglycans. The ECM plays a critical role in mediating cell adhesion, migration, differentiation, and proliferation. Thus, abnormal ECM remodeling can lead to pathological states and cancer metastasis. Fibroblasts, the most abundant cell type in the tumor stroma, produce several ECM components and proteins. Hypoxia (low oxygen level) is a critical factor in cancer growth. The disruption in oxygen homeostasis leads to ECM remodeling. Therefore, many ECM proteins, such as collagens and laminins, are expressed differently. Increased deposition of these proteins can lead to ECM stiffness alterations, which can lead to cancer progression. 3D cell culture methods (spheroids) have gained increasing interest since they provide a more tissue-like environment compared to traditional 2D cell culture methods. We used 3D spheroids containing cancer cells and fibroblasts to mimic cutaneous squamous cell carcinoma (cSCC) tumors. In this study, western blot results showed that in hypoxia, collagen prolyl hydroxylases (P4HA1 and P4HA2) and collagen lysyl hydroxylase (PLOD2) expression increased in both transformed keratinocytes and metastatic cSCC cells when they were cocultured with human primary skin fibroblasts. Laminin-332 expression was, however, downregulated. Immunofluorescence staining confirmed that P4HA1 expression was upregulated in 3D spheroids in hypoxic conditions. Proliferation assay showed that cell proliferation increased in hypoxia in mono- and cocultured spheroids. Mass spectrometry experiments also revealed different ECM protein expressions in hypoxia compared to normoxia. These results show that 3D spheroids containing cancer cells and fibroblasts are an indispensable tool for detecting ECM alterations in hypoxic conditions.
Keywords: ECM proteins, Hypoxia, Cancer 3D spheroid, Collagen, Laminin-332